Making Comments on Making Constitutions - Iorns Magellanes, Catherine (Victoria University of Wellington Law Review, 2002)
This article comments on the "Making Constitutions" seminar panellists’ articles that discuss constitutional reform, including Sir Geoffrey Palmer’s call for a self-reflective society that needs its own constitution, Alison Quentin-Baxter’s balancing act between continuity in the existing system and radical change, Dr Alex Frame’s discussion of constitutional "architects" and "excavators", and Sir John Wallace’s practical reflections on New Zealand’s shift to the MMP system of government. The author provides an overview of themes and lessons from the panellists’ articles, including the value of comparative study, the need for respected advisors and public confidence, and the role of lawyers. The author concludes that any talk of reform must begin imminently to improve New Zealand’s lower level of public awareness about New Zealand’s constitution.